Konsep Perancangan Wisata Kuliner Tempat Pelelangan Ikan Lappa Lelong Sinjai Dengan Penerapan Arsitektur Perilaku - Sulfaida, Sulfaida; Nursyam, Nursyam; Nuryuningsih, Nuryuningsih (TIMPALAJA : Architecture Student Journals, 2023)
Abstract_As a maritime country, Indonesia has vast territorial waters, which have a significant potential for fish resources—culinary tourism to taste the results of natural resources in the ocean. The problem formulation is based on how to design a Lappa Lelong culinary tour to get a qualified design to become a reference for a situation in fish trading places. The data collection method uses three systems, namely: secondary data, where a literature review is carried out; primary data, namely data generated directly or field observations as well as precedent studies, which carry out comparative studies on the design of buildings where fish auctions are held and concepts related to architectural behavior. Geographically, Sinjai Regency is located at 5°2''56" - 5°21''16" south latitude and 119°56''30" - 120°25''33" east longitude. Based on the RTRW of the strategic area with tourism designation, TPI is located in the Lappa village, with site conditions based on observations that are capable and have potential based on the research criteria conducted. This site could be a potential site for developing the fish auction area in Sinjai Regency. For the story of one of the food sectors in Sinjai district, it is necessary to design a lappa lelong culinary tour in Sinjai district with a behavioral architectural approach that can become a more organized forum for people to enjoy fish culinary delights in lappa lelong Sinjai. The design concept used in the design of the lappa auction culinary tour is how to relate the behavior of the use of the designed building.